Iron-Catalyzed C(sp2)–C(sp3) Cross-Coupling Reactions of Di(hetero)arylmanganese Reagents and Primary and Secondary Alkyl Halides - Hofmayer, Maximilian S.; Hammann, Jeffrey M.; Cahiez, Gérard; Knochel, Paul (Synlett, 2018)
An iron-catalyzed cross-coupling between di(hetero)arylmanganese reagents and primary and secondary alkyl halides is reported. No rearrangement of secondary alkyl halides to unbranched products was observed in these C–C bond-forming reactions.
Keywords: iron; catalysis; cross-coupling; manganese; alkyl halides